Disclosure requirements and their assessment by SMEs traded on alternative markets in Poland (NewConnect) and Germany (m:access) - Śliwiński, Paweł; Woźniak, Sonia (Ekonomia i Prawo. Economics and Law, 2022)
Motivation: Financial access limitations are a main barrier to the development of SMEs. One of the methods of bridging the capital gap is SME access to the stock markets, in particular to an alternative market (MTF). Compared to regulated markets, MTFs offer more liberal entry conditions and in many cases prior to MAR implementation they proposed more liberal disclosure requirements. Aim: The aim of the article is to analyze the disclosure requirements resulting from MAR directive and to test their perception by issuers listed on the alternative markets in Poland (NewConnect) and Germany (m:access). The research focused on the assessment of difficulties in performing disclosure requirements and checking whether there is a difference in perceiving the scale of difficulties in fulfilling disclosure duties in both countries. Results: Analysed markets are subject to MAR, so as a rule, there are no differences in the reporting requirements. There is, however, a difference in perceiving them in both countries. The analysis of German issuers shows that, unlike Polish companies, most of them defined their disclosure obligations as simple. This may result from higher knowledge of the regulations than in Poland. The opinion on disclosure requirements by NewConnect issuers had an impact on the amount of time and human resources devoted to disclosure obligations. The research has also shown that issuers in both markets generally assess well the cooperation with authorized advisers who help them, inter alia, in disclosure obligations.